ROLE OF PROBIOTICS IN PREVENTION AND TREATMENT OF ANTIBIOTIC-ASSOCIATED DIARRHEA IN CHILDREN - A. N. Surkov (Педиатрическая фармакология, 2014)
Numerous scientific studies have proved an important role of microbiota in maintaining adequate functioning of the macroorganism and thrown light upon the various issues associated with functional disturbances. Thus, one of the most common causes of intestinal dysbiosis in children is antibiotic therapy, in the setting whereof antibiotic-associated diarrhea (AAD) associated with, but not limited to, pathological activity of Clostridium difficile byproducts — enterotoxin (toxin A), cytotoxin (toxin B) and intestinal peristalsis-inhibiting protein — may develop. However, there are only few published research data on AAD prevalence in children all over the world, which is why it appears impossible to assess the large scale of the problem. That is why it is absolutely necessary to continuously upgrade perception of the role of normal microbiota, etiological factors inducing pathological alterations thereof and approaches to correction of dysbiotic disorders by various medical specialists. Analysis of the current scientific literature demonstrated that AAD prevalence in children varies from 6.2 to 80% depending on the country. The most common (23%) cause of AAD is associated with amoxicillin/clavulanate intake. Moreover, there are data indicating that the AAD development risk is the highest in under-2 children.At the same time, there are data on the protective effect of probiotics, especially of the complex drugs containing a balancedcombination of bifidus and lactic bacteria, on microbiota.